THE CAUCASUS THROUGH THE EURASIAN PRISM - ALIEV, Farkhad (CENTRAL ASIA AND THE CAUCASUS, 2005)
Historians are convinced that the Caucasus has always been an object of close attention of the European states and Oriental Eurasian empires. Throughout the last twenty centuries, the Roman Empire, Persia, Byzantium, and the Ottoman Empire tried to establish their control over the region. Tamerlane, Genghis Khan, Shah Abbas, and Mamai invaded the Caucasus at different times. 1 The founders of a virtual ethnographic museum pointed out: “The Caucasus is a small part of Eurasia, therefore we cannot but marvel at the variety it displays. Its natural conditions range from subtropical to polar; there are large cities and mountain villages comprising a single house-fortress. Christianity, Islam, Judaism, and numerous other very specific beliefs have been living together there.” 2 According to Russian political scientist Alexander Dugin, the Caucasus has been a sphere of strategic rivalry between Russia and the West (the British Empire in the past and the United States today) for three centuries now. Russia was seeking an outlet to the warm seas and the south in order to establish itself in India and the Indian Ocean; Britain, in turn, has been doing its best to stem Russia’s southward thrust. The Caucasian wars, Crimean War, and all Russian-Turkish and Russian-Persian wars were caused by these opposing geopolitical movements. At all times, Britain stood opposed to Russia. Anatoly Gromyko says the same: “In the last few years the region was, according to Kipling, the Great Game unfolded in the 19th century has undergone amazing changes. In the 19th century, Russia and Britain were contending for influence in Central Asia. Later, the Caucasus and Central Asia became part of the zone of vital interests, first, of czarist and, later, of Soviet Russia. Britain concentrated on the Middle East and India. The balance looked immutable until the end of the second millennium, which brought surprises. The Great Game was resumed on a planetary scale. New countries appeared on the political map; these developments made the Caspian Basin the key strategic prize and a future source of energy resources. All of a sudden, the Central Caucasus (Transcaucasus) and Central Asia, which for a long time existed on the periphery of the world community’s attention, developed into a ‘multi-layered pie’ of local, regional, and global interests. Today, they are viewed as vast ‘strait-territories’ with dual civilizational orientations where Christianity and Islam, the West and the East, Europe and Asia, Eurasianism and Atlanticism rub shoulders. The region has any number of active neighbors confronted with vitally important issues. In the north, Russia is trying to extract itself from the vicious circle of economic and political upheavals; in the west, Turkey is balancing between a secular regime sitting on bayonets and moderate Islamism; in the east, China is gaining power; and in the south, there is Iran, which overshadows the Persian Gulf...”4